Permanent Congenital Hypothyroidism in Very Low Birth Weight Infants: A Single Center’s Experience - Joo Hyung Roh; Tae-Gyeong Kim; Keon Hee Seol; Chae Young Kim; Soo Hyun Kim; Ji Yoon Jeong; Ja Hye Kim; Euiseok Jung; Jin-Ho Choi; Byong Sop Lee (Neonatal Medicine)
Purpose Congenital hypothyroidism (CH) is a major preventable cause of intellectual disability, particularly in very low birth weight (VLBW) infants, who are at increased risk due to hypothalamic-pituitary-thyroid axis immaturity. Early differentiation between transient CH (TCH) and permanent CH (PCH) is crucial to optimize L-thyroxine (LT4) treatment duration. This study aimed to determine the incidence of PCH among Korean VLBW infants and to identify clinical factors that may aid in distinguishing TCH from PCH. Methods This retrospective cohort study included VLBW infants diagnosed with CH and treated with LT4 at a single tertiary neonatal intensive care unit between 2011 and 2020. Infants requiring LT4 beyond 3 years were classified as PCH, while those who discontinued earlier were considered TCH. Clinical characteristics, neonatal morbidities, and thyroid-related parameters were compared between the groups. Results Among 1,292 VLBW infants, 122 (9.4%) were diagnosed with CH. After excluding deaths and those lost to follow-up, 73 infants were included in the final analysis (TCH, n=50; PCH, n=23). The PCH group had a significantly higher mean gestational age and greater LT4 requirements at both 12 and 36 months of age. Major anomalies were more frequently observed in PCH infants, including congenital heart defects. In multivariate analysis, higher gestational age, the presence of major anomalies, screening thyroid-stimulating hormone (TSH) >10 μIU/mL, and higher LT4 dose at 36 months were significantly associated with PCH. Conclusion The incidence of PCH in Korean VLBW infants was relatively higher than that reported in previous studies studies. Screening TSH level and LT4 dose requirements may support individualized follow-up and help distinguish PCH from TCH.